Knovel Sampler from works published by: AIChE Center for Chemical Process Safety, Institute of Physics, Knovel Corporation, McGraw-Hill, Plastics Design Library/William Andrew Publishing, SciTech Publishing, ChemTech Publishing. (Knovel, 2003)
This title contains a sample of scientific and technical content available on Knovel. It showcases the range of this content and the benefits of Knovel's productivity tools, such as Graph Digitizer. Use this free title to browse, search (in advanced and basic modes) and practice the use of productivity tools.
Keywords: Knovel (Firm) -- Bibliography.; Engineering -- Computer network resources.; Chemical engineering -- Computer network resources.; Chemistry -- Computer network resources.; Plastics -- Design -- Computer network resources.; elektronické knihy; electronic books